2018
DOI: 10.19080/artoaj.2018.18.556063
|View full text |Cite
|
Sign up to set email alerts
|

Durum wheat (Triticum durum Desf) Variety “Utuba” Performance in Ethiopia

Abstract: Durum wheat (Triticum durum Desf.) is industrial and a staple food crop of Ethiopians. Produced in most parts of Ethiopia and has existed in Ethiopia for thousand years. Annually, it occupies 500 thousand hectares in the country. However, the national average yield of durum wheat is low 2.2 t ha-1. The use of unimproved local cultivars and biotic and a biotic stresses are partially attributed to the low yield of the crop. Thus, the experiment was designed to develop high yielding, disease resistant and desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…'Utuba' was released in 2015 as an alternative variety to 'Mangudo' and 'Mukuye' because of its amber seeds, high protein content and high yield potential. The grain yield performance on research station ranged from 3.4 to 6.5 t ha −1 and from 2.5 to 4.5 t ha −1 in farmers' fields [63]. 'Utuba' (Omruf1/Stojocri2/3/1718/BeadWheat24//Karim) takes on average 62 days to flower, 108 days to mature and it is also appreciated for its height (80-90 cm), which ensures good amount of straw for the livestock.…”
Section: Durum Wheat In East Africa As a Staple And Cash Cropmentioning
confidence: 98%
“…'Utuba' was released in 2015 as an alternative variety to 'Mangudo' and 'Mukuye' because of its amber seeds, high protein content and high yield potential. The grain yield performance on research station ranged from 3.4 to 6.5 t ha −1 and from 2.5 to 4.5 t ha −1 in farmers' fields [63]. 'Utuba' (Omruf1/Stojocri2/3/1718/BeadWheat24//Karim) takes on average 62 days to flower, 108 days to mature and it is also appreciated for its height (80-90 cm), which ensures good amount of straw for the livestock.…”
Section: Durum Wheat In East Africa As a Staple And Cash Cropmentioning
confidence: 98%
“…Utuba variety performs better at Gimbichu, Bishoftu and Minjar when compared with Tesfaye variety. The findings of Temtme, indicated that Utuba variety was released with advantages of grain yield performance ranging from 2.5t ha-1-4.5 t ha-1 on farmers field [19].…”
Section: Grain Yield Performance Of Durum Wheatmentioning
confidence: 99%
“…However, the national average yield of durum wheat is low 2.4 t ha-1. The use of unimproved local cultivars and biotic and abiotic stresses are partially attributed to the low yield of the crop [19]. Compared to bread wheat, the most common alternative, durum wheat is appreciated by farmers mainly for its resistance to biotic and abiotic stress, better food quality, better weed competition, and straw production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…'Utuba' was released in 2015 as an alternative variety to 'Mangudo' and 'Mukuye', because of its amber seeds, high protein content and high yield potential. The grain yield performance on research station ranged from 3.4 to 6.5 t ha -1 and from 2.5 to 4.5 t ha -1 in farmers' fields [53]. 'Utuba' takes 62 days to (head) and 108 days to mature, and it is also appreciated by its good height (82 cm), which ensures good amount of straw for the livestock.…”
Section: Durum Wheat In East Africa As a Staple And Cash Cropmentioning
confidence: 99%